Functionalized SBA-15 and its catalytic applications in selective organic transformations - Srinivas, Darbha; Saikia, Lakshi (Catalysis Surveys from Asia, 2008)
Ordered, mesoporous SBA-15 functionalized with organic and inorganic moieties exhibits efficient catalytic activity in a variety of organic transformations. In this account, reviewing our own work, three-sets of surface-modified SBA-15 materials have been investigated. The first-set of materials consists of SBA-15 modified with organo-acidic (propyl thiol and propyl sulfonic acid) and basic (propyl amine and propyl adenine) moieties. The second-set of materials was prepared by grafting Mn complexes to the organo-functionalized SBA-15. The third-set composes of nanocrystalline metal oxides supported on SBA-15. All these catalysts have been characterized by structural and spectroscopic techniques. Catalytic activities of the first-set of solid materials have been investigated in acid/base-catalyzed reactions viz., ring-opening of epoxides with amines (producing beta-amino alcohols), esterification, three-component-Mannich reactions and cycloaddition of CO(2) to epoxides. The Mn complexes grafted on organofunctionalized SBA-15 are efficient catalysts for the chemo-, regio- and stereoselective aerial oxidation of monoterpenes at ambient conditions. TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 catalyzed biomimetic oxyhalogenation of aromatic compounds. In all these reactions, the functionalized SBA-15 showed high selectivity.
Keywords: grafted Mn-Salen complexes; Ordered mesoporous silica; organofunctionalized SBA-15; oxidation catalysts; Oxyhalogenation of aromatics

Factors Influencing the Kinetics of Esterification of Fatty Acids over Solid Acid Catalysts - Satyarthi, Jitendra Kumar; Radhakrishnan, Sambhu; Srinivas, Darbha (Energy & Fuels, 2011)
The kinetics of esterification of fatty acids with alcohols over three different solid acid catalysts, viz., large pore zeolite-beta (H beta), micro-mesoporous Fe-Zn double-metal cyanide (DMC), and mesoporous Al-MCM-41, have been reported. Hydrophobicity of these catalysts increases in the order: Al-MCM-41 < H beta < DMC. The chain lengths of the fatty acid (C(8.0)-C(18.1)) and alcohol (C(1)-C(8)) molecules have been varied, and their influence on kinetic parameters has been studied. The present study reveals that porosity and surface hydrophobicity of the catalyst are the two important factors other than acid properties (concentration and strength of acid centers) that influence the esterification reaction.

Fourier transform infrared spectroscopic method for monitoring hydroprocessing of vegetable oils to produce hydrocarbon-based biofuel - Satyarthi, Jitendra K.; Srinivas, Darbha (Energy & Fuels, 2011)
A novel Fourier transform infrared spectroscopic method is reported, for the first time, to estimate the conversion of vegetable oil (soybean oil, for example) to hydrocarbon-based biofuel via hydroprocessing. The infrared peak attributed to the carboxyl group (O-C=O) is used as a marker to determine the conversion of fatty acid glycerides in soybean oil to hydrocarbons. Unlike the conventional gas chromatographic method, this new method of estimation is fast and requires no derivatization of the sample and predetermination of response factors of each chemical component in vegetable oil/product samples. H-1 and C-13 nuclear magnetic resonance spectroscopy techniques are also reported to substantiate and confirm the purity and product formation in the hydroprocessing reaction.

Factors influencing catalytic activity of Co-Zn double-metal cyanide complexes for alternating polymerization of epoxides and CO2 - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2015)
Co-Zn double-metal cyanides (DMCs) show good catalytic activity towards copolymerization of epoxides and CO2. A deep insight into the structural aspects of the catalysts that control their catalytic performance is addressed in this work. Method of preparation of DMC catalysts was found to have influence on their structure, which in turn dictated their catalytic activity. Complexing agent (t-BuOH) and density of strong acid sites of DMC catalysts were found critical factors responsible for their activity. Selectivity of DMC towards polycarbonates depends on the amount of alkali ion content in their composition. Induction period of the catalysts was governed by the strength of acid sites and by the presence of dispersed ZnCl2 in the composition. This study provides an understanding of the prime features of DMC catalysts that can be tuned for high productivity of polycarbonates. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Copolymerization of epoxides and CO2; Double-metal cyanide; Polycarbonate